Couple relationships as a factor related to the practice of breast self-examination in university students - Martín-Díaz, Anaid Guadalupe; Campos-Uscanga, Yolanda; Gutiérrez-Sida, Claudia (Universidad y Salud, 2018)
Introduction: There is controversy about the relationship between beliefs and the realization of breast self-examination in women and there is a lack of studies which show the influence that couples can have in that practice. Objective: To identify whether there is an association between breast self-examination, lifestyles, health beliefs, and partner relationships in university students. Materials and methods: A cross-sectional study was conducted with 284 women students from the University of Veracruz. The Health beliefs questionnaire was applied to breast self-examination and a personal data questionnaire. Results: The average age was 20.32. Only 19.7% of the students reported the realization of breast self-examination monthly. Women who did not have a couple showed greater barriers to self-examination and lower perceived benefits. Age favored the realization of breast self-examination, while the perceived barriers limited it. On the other hand, having a couple was associated with lower barriers and increased benefits to self-examination. Conclusions: There is low self-examination in the students despite their knowledge. Having a couple decreases the perceived barriers to conducting breast self-examination.